Ovine lentivirus-induced disease: early pulmonary inflammation and viral replication - Keane, Kevin Allan, author; DeMartini, James C., advisor; Akkina, Ramesh, committee member; Mason, Gary L., committee member; Howell, Mark, committee member (Colorado State University. Libraries, 2001)
Ovine lentivirus (OvLV) is the etiologic agent of lymphocytic interstitial pneumonia (LIP). LIP is a common, naturally occurring disease among sheep and is a model of a similar disease in humans infected with human immunodeficiency virus. Since there is considerable uncertainty as to earliest sequence of events in the hostlentivirus relationship, this investigation was undertaken to better define the factors that contribute both to pulmonary inflammation and viral replication. This was accomplished by an in vivo investigation of lambs experimentally inoculated with OvLV and in vitro studies examining lymphocyte proliferation and lentivirus replication. The lambs inoculated with OvLV were examined for pulmonary lesion development through bronchoalveolar lavage cell analyses and histological analyses at either two, four, or 18 weeks post inoculation (PI). Inflammation peaked four weeks PI with accumulations of peribronchiolar T cells and numerous alveolar macrophages. Macrophages had increased expression of MHC II but were spatially separated from the lymphoid cell accumulation. The degree of lymphoid cell accumulation was predictive of the virus infection rate of alveolar macrophages. Lymphocyte proliferation was tested in vitro with mitogenic (concanavalin A) and antigenic (OvLV) stimulation, both with and without alveolar macrophages. Lymphocytes from OvLV inoculated lambs responded weakly to IV mitogenic stimulation compared to the medium inoculated lambs and the proliferative responses from both sets of animals was suppressed when co-cultured with autologous alveolar macrophages, regardless of whether the macrophages were infected. Finally, monocyte derived macrophages infected with lentivirus in vitro produce more new virus when inducible nitric oxide synthase is blocked by the amino acid analogue aminoguanidine. The blockage could be reversed when L-arginine was present at greater concentrations than aminoguanidine. The addition of exogenous nitric oxide to the culture did not influence OvLV replication rates. Collectively, these data suggest that exuberant T cell mediated pulmonary inflammation increases the recruitment of macrophages to the lung and the potential for infectious spread within the host. The subsequent control of virus replication may be due in part to the innate immune mediator nitric oxide.
Keywords: pathology; immunology